All Days 2018
DOI: 10.2118/192388-ms
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency Static Mixer Technology for Crude Desalting

Abstract: A high-efficiency static mixer was installed at the inlet of a desalter vessel at a Saudi Aramco gas-oil separation plant (GOSP) under an initiative to field trial new technologies to enhance crude quality of low water and salt content, and to optimize wash water consumption used in the desalting. This paper describes a high-efficiency static mixer assessment through Computational Fluid Dynamics (CFD) modeling and an extensive field trial. The technology, which is the first of its kind implemented in Saudi Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Nasser A. A et al [14] The installation method for the static mixer in the electric desalination process A total saving of more than 8.5 million gallons of wash water was achieved during the nine months of the field trial.…”
Section: Researchers Factor Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasser A. A et al [14] The installation method for the static mixer in the electric desalination process A total saving of more than 8.5 million gallons of wash water was achieved during the nine months of the field trial.…”
Section: Researchers Factor Conclusionmentioning
confidence: 99%
“…Most of the studies on static mixers have been carried out using Computational Fluid Dynamics (CFD), except for Hammoudi's work, which is experimental (Table 1) [13,14]. However, these studies mainly focus on the influence of static mixers (such as the shape and thickness of the mixing elements [15,16] and the type [17][18][19]) and the properties of the mixed liquid [20][21][22][23] on the oil-water mixing effect, and they only discuss the transmission process without delving into the mass transfer process of salt washing efficiency in the electric desalination process.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new design of a high-efficiency static mixer located at the inlet of the desalting unit was modeled by CFD techniques and field trials by Alhajri et al [20] in a Saudi Arabia refinery. They concluded that enhancing turbulence is the key to saving wash water and improving water and salt removal efficiency.…”
Section: Novel Electrostatic Device Consisting Of Separation Cellsmentioning
confidence: 99%